Infection rates in tacrolimus versus cyclosporine‐treated pediatric kidney transplant recipients on a rapid discontinuation of prednisone protocol: 1‐year analysis. (31st March 2017) - Kizilbash, Sarah J.; Rheault, Michelle N.; Bangdiwala, Ananta; Matas, Arthur; Chinnakotla, Srinath; Chavers, Blanche M.
Abstract: AR is lower in pKTx recipients on Tac vs CsA. Data comparing infection outcomes for children treated with these agents are limited. We retrospectively studied infection outcomes in 96 pKTx recipients on a RDP. PS, DCGS, AR, and infection‐free survival were assessed using Kaplan‐Meier/log‐rank tests and proportional hazards models. There were no differences in 1‐year PS, DCGS, or AR between Tac and CsA recipients. After adjusting for AR, the hazard of CMV viremia was 4.0 times higher (95%CI: 1.04, 15.5; P = .044) and that of BK viremia was 3.8 times higher (95%CI: 1.5, 10.2; P = .007) in Tac recipients. The incidence of EBV viremia was similar between the groups ( P = .56). PostTx lymphoproliferative disease was only observed in Tac recipients (3%). There was no difference in the incidence of pneumonia, urinary tract, or Clostridium difficile infections between Tac and CsA recipients. Among KTx recipients on RDP, the hazards of CMV and BK viremia within 1 year post‐KTx were significantly higher in Tac recipients compared to CsA. Regular assessment for infections and lower Tac trough levels may be warranted in Tac recipients.